URBAN REGENERATION AND TOURIST DEVELOPMENT: THE CASE OF THE FORMER INDUSTRIAL SUBURB OF BAGNOLI (NAPLES, ITALY) - Silvia IACUONE (Analele Universităţii din Oradea: Seria Geografie)
This article analyses the tourist perspectives of former industrial suburbs through the case study of Bagnoli (Naples, Italy). In fact, despite at the end of XIX century the district of Bagnoli was an emerging seaside and thermal area, in 1910 it was chosen as the location of a huge iron and steel industrial plant. Even today, unfortunately, the district is characterized by dismissed facilities and a heavy industrial landscape that constitute a landmark. However, at the same time, Bagnoli still retains great potential and tourist resources, which could help it in the process of urban regeneration and recovery of tourism, until now largely hampered by bureaucracy, corruption and incapacity of the political class. After a qualitative analysis of the existing literature, a field analysis was conducted, in order to observe the resources of the territory and the strong dualism with the former industrial landscape. Finally, to support the analysis, a questionnaire was submitted to the residents of Bagnoli in which a renewed optimism for the regeneration of the neighborhood emerged, but also a strong awareness of the weakness of the institutions.